KDM3 epigenetically controls tumorigenic potentials of human colorectal cancer stem cells through Wnt/β-catenin signalling - Jiong Li (Nature Portfolio, 2017)
Epigenetic factors can regulate functional properties of human colorectal cancer stem cells. Here, the authors show that histone demethylases of the KDM3 family activate Wnt signalling in colorectal cancer stem cells by erasing H3K9me2 marks on Wnt target genes and recruiting MLL1 to promote H3K4 methylation.